Iliotibial band syndrome (ITBS) - Migliorini, S.; Merlo, M.; Migliorini, L. (Triathlon Medicine, 2019)
Iliotibial band syndrome (ITBS) is an overuse injury caused by repetitive friction of the iliotibial band and the underlying bursa or lateral recess across the lateral femoral epicondyle. ITBS is a well-known cause of lateral knee pain in endurance sports and particularly in long-distance runners. Friction occurs near foot strike, predominantly in the foot contact phase, at, or slightly below, 30° of flexion. The ITBS is usually caused by a combination of intrinsic and extrinsic factors and must be evaluated also the biomechanics of running and the training programme. Imaging (MRI, echography) is not usually required to confirm the diagnosis of ITBS. The conservative treatment includes the activity modification, the soft tissue therapy, the electrotherapeutic modalities, the corticosteroid injection and the correction of the biomechanical abnormalities. The personal ITB surgical release performed by the authors may be indicated if the conservative management fails and it is a safe procedure to return to practice sports at the same level.